Role of Doppler ultrasonography of the splenoportal system in diagnosing early hepatic dysfunction in non-alcoholic fatty liver disease patients - Safeeq Ahmed Meeran S; Nancy Dora S; Barakath Nisha A (Asian Journal of Medical Sciences, 2023)
Background: Non-alcoholic fatty liver disease (NAFLD) has emerged as a global and national epidemic. This is due to a sedentary lifestyle, unhealthy food habits, obesity, and metabolic syndrome prevailing among young and middle-aged individuals. Clinical diagnosis of NAFLD is difficult as most of the patients are asymptomatic. NAFLD can be assessed using an imaging system. Ultrasonography is the most widely used first-line initial imaging modality of choice. Aims and Objectives: To assess the role of Doppler ultrasonography of the splenoportal system in NAFLD patients. Materials and Methods: It is a hospital-based single-center cross-sectional study that collects data on patients who meet the inclusion criteria. A diagnosis of NAFLD will be made based on clinical and ultrasound workup. Then, Doppler Ultrasonography examination of the abdomen of the selected patient was done and assessed for different parameters. Results: It was observed that there was a significant decrease in portal vein velocity and its pulsatility index, a decrease in hepatic artery resistive index and pulsatility index, a reduction of hepatic vein phasicity, an increase in liver size and portal vein diameter with increasing severity of fatty liver. It is inferred that apart from assessing the hemodynamic changes in the portal circulation, we can also predict early portal hypertension and hepatic fibrosis. Conclusion: Doppler ultrasonography of the splenoportal system can be used to predict early fibrosis, portal hypertension, and thus cirrhosis.